A variant of variola virus, characterized by changes in polypeptide and endonuclease profiles. - Dumbell, K. R. (Cambridge University Press, 1999)
A variant of variola virus is described which produces a late polypeptide of 25 kDa instead of one of 27 kDa and which has an additional endonuclease cleavage site for SalI in the viral DNA. These markers were shown to be genetically independent and to characterize 14 of the 48 variola strains which were examined. The variant strains were isolated from smallpox outbreaks originating in or from Pakistan between 1961 and 1974 and also from two cases at a Mission Hospital in Vellore, India in 1964. No variant strains were found among 9 other isolates from cases of variola major occurring in other parts of India or in Bangladesh, nor among 4 isolates from Indonesia, 15 from Africa or 6 isolates of variola minor.